Android-based FTKI UNAS Employee Performance Monitoring System Using Rating Scale Method: Android-based FTKI UNAS Employee Performance Monitoring System Using Rating Scale Method - Wardana, Adi Agungkusuma; Fauziah, Fauziah; Nathasia, Novi Dian (Institute of Computer Science (IOCS), 2020)
A system is needed to be used to improve the quality of human resources. Performing performance appraisals is the system that will be used. Employee performance appraisal has a main function in the work environment. This problem is related to the provisions achieved by the company, related to the performance of its employees. The monitoring system of the performance appraisal of the FTKI Secretariat staff at the National University is still fairly manual due to the absence of applications to assess the performance of its employees. Assessing the ability of employees when implementing Rating Scale is the purpose of this study at the FTKI Secretariat at the National University. Many companies currently apply very global and very simple methods through rating scales. To evaluate the ability of this employee to use the rating scale method, if starting from the scale of